Ibn Sina’s contributions to modernity: integrating medieval philosophy, neurophilosophy, and educational reform in Islamic thought and civilisation - Norman, Nurul Ain; Ruhullah, Mohammad Eisa (International Institute of Islamic Thought and Civilisation (ISTAC-IIUM), 2024)
This study explores the enduring legacy of Ibn Sina, a seminal figure in Islamic medieval philosophy, focusing on his theory of the soul and its implications for modern neurophilosophy, educational reform, and the renewal of Islamic thought and civilisation. By bridging the intellectual heritage of Ibn Sina with contemporary discussions in neurophilosophy, this paper highlights his contributions to understanding the nature of consciousness, perception, and the human mind. Furthermore, it examines how Ibn Sina's insights can inform modern educational practices, advocating for an integration of classical wisdom and scientific advancements within the curriculum of Islamic studies. This integration not only pays homage to the rich intellectual tradition of Islamic civilisation but also fosters a dialogue between the medieval and the modern, contributing to the ongoing process of renewal and reform in Islamic thought. By applying Ibn Sina’s philosophical principles to contemporary challenges in education and society, this research underscores the potential for medieval Islamic philosophy to contribute to modernity, offering innovative pathways for navigating the complexities of the 21st century.